RISK CULTURAL EVALUATION AS ORGANIZATIONAL CULTURE IN THE TAX SERVICE OFFICE - Bandiyono, Agus; Pratama, Lazuardi Widyanto (Dinasti Publisher, 2019)
The objectives to be achieved in this study are to evaluating risk management practices in the form of a risk awareness culture and identifying factors inhibiting the implementation of a risk awareness culture at the Pondok Aren Primary Tax Service Office. The research method used to obtain and analyze data that can support this writing is a qualitative method through interviews and document collection through library research. The implementation of the Risk Awareness Culture as a whole has been following the implementation guidelines namely Regulation of the Minister of Finance No. 12 / PMK.09 / 2016 namely leadership who is committed to considering risks in every decision making, ongoing communication to all levels of the organization regarding the importance of risk management, respect for those who can manage risk well, and integrate risk management in organizational processes. However, in practice, the implementation of the 2016 risk awareness culture at KPP Pratama Pondok Aren encountered several obstacles. The obstacles are in the form of a lack of reward (reward) at the Pondok Aren Primary KPP and the Human Resources aspect at Pondok Aren Pratama KPP